2022
DOI: 10.3390/molecules27155005
|View full text |Cite
|
Sign up to set email alerts
|

Chitin Isolation and Chitosan Production from House Crickets (Acheta domesticus) by Environmentally Friendly Methods

Abstract: Alternative methods were evaluated for chitin isolation from Acheta domesticus. Chemical demineralization was compared to fermentation with Lactococcus lactis, citric acid treatment, and microwave treatment, leading to a degree of demineralization of 91.1 ± 0.3, 97.3 ± 0.8, 70.5 ± 3.5, and 85.8 ± 1.3%, respectively. Fermentation with Bacillus subtilis, a deep eutectic solvent, and enzymatic digestion were tested for chitin isolation, generating materials with less than half the chitin content when compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
0
10
1
Order By: Relevance
“…The %DM is not commonly reported in the scientific literature. However, Psarianos et al [34] published a %DM of 91.1 ± 0.3% using 1 M HCl for 2 h at 98 • C for house crickets, in comparison to the 95.85 ± 0.012% achieved in our study. Based on these results, it can be concluded that a successful standardization of the DM process was achieved.…”
Section: Standardization Of Dm Processcontrasting
confidence: 80%
“…The %DM is not commonly reported in the scientific literature. However, Psarianos et al [34] published a %DM of 91.1 ± 0.3% using 1 M HCl for 2 h at 98 • C for house crickets, in comparison to the 95.85 ± 0.012% achieved in our study. Based on these results, it can be concluded that a successful standardization of the DM process was achieved.…”
Section: Standardization Of Dm Processcontrasting
confidence: 80%
“…Compared to the biological method to isolate chitin, the chemical method always produces a higher output of crude chitin. This observation applies to insect chitin as well [29][30]. Values represent means ± SD (n = 3).…”
Section: Deproteinization Rate and Crude Chitin Yieldmentioning
confidence: 78%
“…Bands between 890-1,156 cm -1 indicate the polysaccharide structure for chitin. Other functional groups identified were: bands between 3,100 and 3,273 cm -1 (N-H stretching of the amide group); 2,932 and 2,934 cm -1 (asymmetric stretching vibration of CH 3 and CH 2 groups); 2,889 and 2,891 cm -1 (C-H stretching); 1,376 and 1,382 cm -1 (symmetrical deformation mode of CH 3 ); 1,320 to 1,340 cm -1 (methyl C-H stretch of amide III); 1,158 and 1,159 cm -1 (asymmetric stretching of the C-O-C bridge) [17,[29][30]. The consistent wavenumbers of amide I and II functional groups indicate the effectiveness of deproteinization [30] using crude enzyme extracts from winter wheat and buckwheat.…”
Section: Fourier Transform Infrared (Ftir) Spectroscopy Analysismentioning
confidence: 99%
“…An alternative technique for chitin separation from A. domesticus has also been proposed [165]. The relative degrees of demineralization for chemical demineralization, citric acid treatment, Lactococcus lactis fermentation, and microwave therapy were 91.1, 70.5, 97.3, and 85.8%, respectively.…”
Section: House Cricketmentioning
confidence: 99%